Comparison of the expression and spatial localization of glucose transporters in the rat, bovine and human lens. (August 2017) - Lim, Julie C.; Perwick, Rebecca D.; Li, Bo; Donaldson, Paul J.
Abstract: The energy required to drive lens transparency is derived from the metabolism of glucose. In the lens, the uptake of glucose is likely to involve either facilitative glucose uptake mediated by members of the GLUT family or Na + dependent glucose uptake via members of the SGLT family, or both. While GLUT1 and GLUT3 have previously been identified in the rat lens, the expression of SGLTs is unknown. Since antibodies directed against the N and C-terminal epitopes of the GLUT and SGLT family are now commercially available, the purpose of this study is to extend our screening of glucose transporters in the rat lens to include the SGLTs and compare the expression profiles of GLUTs and SGLTs in the different regions of the rat, bovine and human lens. Using a combination of reverse transcriptase PCR, western blotting and immunohistochemistry, we have shown that GLUT1 appears to be the predominant glucose transporter in the rat lens since it was expressed in all regions of the lens. In contrast GLUT3, SGLT1 and SGLT2 had more restricted expression patterns and were only found localised to the inner cortex and core regions of the rat lens. GLUT1 was the only transporter found in the epithelium and appears to exist as a full length form in this region, while in differentiating fiber cells; GLUT1 appears to undergo a modification to its N-terminus. Translating our work to bovine and human lenses revealed that GLUT1 is the only glucose transporter expressed in bovine and human lenses. While GLUT1 in the bovine lens appears to be unmodified throughout the entire lens, GLUT1 in human lenses appears to be N-terminally modified in all regions, including the epithelium. Finally, it appears that GLUT1 expression is maintained in all regions of the human lens with increasing age indicating that there is no further regional or age-dependent processing of GLUT1 in the human lens. Taken together, these studies have identified GLUT1 to be the primary transporter that mediates glucose uptake in the rat, bovine and human lens. Highlights: Identified facilitative and Na + dependent glucose uptake transporters in the rat lens. GLUT1 is the predominant transporter expressed in the lens epithelium and outer cortex. GLUT3, SGLT1 and SGLT2 were identified in the deeper regions of the rat lens. Translational studies reveal GLUT1 to be the only glucose transporter expressed in bovine and human lenses. These studies highlight the differences in glucose uptake transporters between the rat, bovine and human lens.